Punishment in Islamic Early Childhood Education: Harmonizing Islamic Principles and Educational Theories - Ginting, Dea Nitami Br; Munisa, Munisa (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study explores the permissibility and application of punishment in Islamic early childhood education by integrating Islamic principles and educational theories. Using a qualitative library research approach, the study analyzes books and journal articles to understand the purpose, conditions, and ethical boundaries of punishment. The findings reveal that punishment is allowed in both frameworks if administered wisely—without physical or psychological harm—and aimed at behavioral improvement. Islam and modern education agree that punishment should follow love, advice, and awareness-building strategies. This study emphasizes the importance of conscious, proportional, and compassionate disciplinary practices in shaping children's moral development.